Transforming Global Food Systems: Pathways to Sustainability, Resilience and Equity - , J.R. Shalini; , G.S. Sreedaya; , Chinchu V.S.; , Riza Mathew (Archives of Current Research International, 2025)
The global food system is at a critical stage, facing unprecedented challenges threatening its ability to sustainably feed a growing population. This paper explores the multifaceted issues faced by current food systems, including environmental degradation, inequitable access, and inefficiencies that compromise both human and ecological health. We analyze the urgent need for a transformative approach that addresses these challenges and aligns with the Sustainable Development Goals (SDGs), particularly those focused on hunger, health, and sustainable production. The paper argues that a reimagined food system must be sustainable, resilient, and equitable to ensure long-term food security and social justice. By examining case studies of innovative practices and policies, we highlight pathways for systemic change that can foster environmental stewardship, economic viability, and social inclusion. This highlights the importance of integrating sustainability principles into food system transformation efforts to create a more robust framework for future food security.